2021
DOI: 10.3991/ijoe.v17i14.27371
|View full text |Cite
|
Sign up to set email alerts
|

EduGram: Education Development Based on Hologram Technology

Abstract: Education is one of the most important areas of life that affect the development and progress of societies, and the usage of images and visual representation methods is of real value in the educating process. Over time, different simple methods were used to display the information visually, which mostly are considered weak methods that may not perform its full purpose and the information may be transferred slowly and in an incomplete manner.  Technology has contributed from the beginning of its emergence in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…According to Ahmad et al [ 50 ], Augmented Reality (AR) differs from 3DHT in that it displays 3D objects that cannot be seen by the naked eye. It can be experienced by wearing AR glasses or using a smartphone to display a virtual 3D image on the screen.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ahmad et al [ 50 ], Augmented Reality (AR) differs from 3DHT in that it displays 3D objects that cannot be seen by the naked eye. It can be experienced by wearing AR glasses or using a smartphone to display a virtual 3D image on the screen.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A Hologram LED-fan projector device (HLFP) was used in this study, as shown in ( Fig 3 ). The HLFP was extensively used in the field of education [ 47 , 50 , 51 ]. It is capable of displaying 3D graphics through rapid rotation, but does not produce sound.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Technological advances in the era of society 5.0 have the opportunity to improve the quality of education in achieving creative, interactive, and innovative learning processes which can compete with countries with the best education systems in the world such as Finland, Japan, the United States, Canada, etc. Moreover, technology in education provides easy access to information in delivering learning materials which can be positive, relevant, and effective solutions to support distance learning [8]. In addition, the learning process should provide easiness in delivering materials to create a more lively and interactive learning atmosphere integrated with technology in building visualized learning media.…”
Section: Introductionmentioning
confidence: 99%
“…In the wake of deepening global digitization and the rapid advancement of AI technology, artificial intelligence (AI) has permeated various aspects of daily life [1][2][3][4][5][6][7][8][9][10]. Against this backdrop, education, a crucial domain dedicated to nurturing future generations and enhancing the overall quality of society, has naturally emerged as one of the primary applications of AI technology [11][12][13].…”
Section: Introductionmentioning
confidence: 99%